Becoming an inventor: a young Latina’s narrative - Sáenz, Cristina; Skukauskaitė, Audra; Sullivan, Michelle (Frontiers in Education, 2024)
Our article is well-suited for the special edition issue of Frontiers Invention Education and STEM: Perspectives and Possibilities because we focus on the exploration of how the life experiences of a young Latina student played a significant role in the formation of her identity as an inventor. This research aims to shed light on an underexplored topic concerning the development of inventor identities among underrepresented students in the context of invention education. By closely examining the narrative of a high school aged Latina inventor, we gain valuable insights into the process of identity construction through repeated identity work. This analysis aligns with previous research conducted by Calabrese-Barton et al. (2013), Couch et al. (2018), and Kelly et al. (2013), thereby reinforcing their findings. Furthermore, our study is significant in providing diverse perspectives on invention education from underrepresented students. It deepens our understanding of the broader implications of invention education in the lives of young people of color. Our study contributes to the growing body of literature which emphasizes the importance of increased access and opportunities for diverse students to participate in invention education.